A birth cohort study of viral infections in Vietnamese infants and children: study design, methods and characteristics of the cohort - Simmons, Cameron (2018)
BACKGROUND: In Ho Chi Minh City, Vietnam, more than one-third of admissions to the two paediatric hospitals are attributable to four infectious syndromes: dengue, diarrhoeal disease, acute respiratory infection, and hand, foot and mouth disease. We have established a large prospective birth cohort study to investigate individual, environmental, virological, and immunological determinants of infection and disease in infants. Specific research questions are focused on the role of maternal antibody in protection against infection in infancy, and the adaptive immune response to vaccination and natural infection. This paper presents the cohort design, methods, and baseline characteristics of the participants enrolled in the first two years. METHODS/DESIGN: Women are enrolled prior to delivery at one hospital in each of two catchment areas: an urban district in central HCMC, and a mixed urban/rural district in the Mekong Delta 150 km southwest of HCMC. Infants are enrolled within 3 days of birth, and maternal and cord blood samples are collected. Routine blood samples and data on growth, health status and vaccinations are collected from infants at scheduled visits at 4, 9 and 12 months. Clinical data and specimens are collected from infants presenting at a study clinic, or admitted to hospital, with any of the the four infectious syndromes of interest. DISCUSSION: In four years since since the study began in July 2009, >6400 infants have been enrolled, and enrolment is ongoing. Attrition is low: 84% of participants have completed the full 12-month follow-up period. Baseline characteristics of the first 4300 enrollees are presented here. We have demonstrated the feasibility of establishing a large prospective study of infectious diseases in infancy in a resource-limited setting, with minimal loss to follow-up. Our linked socio-demographic, clinical and laboratory data will help elucidate the viral aetiology and epidemiology of common infectious diseases of infancy, and can inform the implemention of existing and future vaccines. This study furthermore provides a platform to which additional endpoints could be added in the future.